Prognostic factors in progressive high-grade glial tumors treated with systemic approach: A single center experience - ATASOY, BESTE MELEK; DANE, FAYSAL; EKİNCİ, GAZANFER; ZİYAL, MUSTAFA İBRAHİM; DEMİRCAN, NAZIM CAN; YUMUK, PERRAN FULDEN; ARIKAN, RUKİYE; BOZKURT, SÜHEYLA; BAŞOĞLU TÜYLÜ, TUĞBA; AKIN TELLİ, TUĞBA; BAYRİ, YAŞAR (SAGE PUBLICATIONS LTD, 2021)
Purpose Malignant high-grade gliomas are the most common and aggressive type of primary brain tumor, and the prognosis is generally extremely poor. In this retrospective study, we analyzed the outcome of systemic treatment in recurrent high-grade glioma patients and the impact of prognostic factors on survivals. Methods Data from 114 patients with recurrent high-grade glioma who received systemic treatment and followed in our clinic between 2012 and 2018 were retrospectively analyzed. Eastern Cooperative Oncology Group (ECOG) performance status, age, gender, histology, type of surgical resection, side effects after systemic treatment (deep vein thrombosis, hypertension, proteinuria), IDH1 and alpha thalassemia/mental retardation syndrome X-linked (ATRX) mutation status were investigated as prognostic factors for progression-free survival and overall survival. Results At the time of diagnosis, the median age was 48 (17-77) and 68% of the patients were male. Most common pathologic subtype was glioblastoma multiforme (68%). Median follow-up duration was 9.1 months (1-68 months). Median progression-free survival and overall survival were 6.2 months and 8 months, respectively. In multivariate analysis, ECOG PS, deep venous thrombosis and the presence of ATRX and IDH1 mutation were found to be independent prognostic factors for progression-free survival (p < 0.05) and, ECOG PS, the presence of ATRX and IDH1 mutation for overall survival (p < 0.05). Conclusion Our study is real life data and the median progression-free survival and overall survival rates are similar to the literature. We have found ECOG PS, presence of ATRX and IDH1 mutation to be independent prognostic factors for both progression-free survival and overall survival.
Keywords: High-grade gliomas; glioblastoma multiforme; ATRX status; IDH status; thrombosis; BEVACIZUMAB-INDUCED HYPERTENSION; CENTRAL-NERVOUS-SYSTEM; VENOUS THROMBOEMBOLISM; ADJUVANT TEMOZOLOMIDE; GLIOBLASTOMA; ATRX; MUTATIONS; SURVIVAL; GLIOMA; IDH1